HUBUNGAN PERILAKU GIZI SEIMBANG DENGAN STATUS GIZI REMAJA - Ravi Masitah; Amelia Prahastuti (IKesT Muhammadiyah Palembang, 2024)
Background: Adolescents with poor nutritional status will have an impact on low intelligence, productivity and body immunity, while higher nutritional status can cause an increased risk of non-communicable diseases. Research Method: This research is an analytical research with a cross sectional research design. The research uses primary data, namely data collected by the researcher himself in the form of data on general characteristics, balanced nutritional behavior and nutritional status of adolescents. The research also used secondary data from IKesT Muhammadiyah Palembang for the number of undergraduate students in Nutrition at IkesT Muhammadiyah Palembang. Results: Based on the results of statistical tests, it shows that there is a relationship between balanced nutritional behavior and adolescent nutritional status (p value = 0.000). The level of strength of the relationship is strong with a correlation coefficient value of 0.597. The variable relationship is unidirectional, which means that the better the balanced nutritional behavior, the better the nutritional status. Conclusion: The results of the study show that there is a relationship between balanced nutritional behavior and adolescent nutritional status, p-value 0.000 < 0.05. Balanced nutritional behavior can help teenagers maintain normal nutritional status and prevent nutritional problems